(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Introduction: Typhoid fever, caused by S. Typhi, is prevalent in developing countries, particularly the Indian subcontinent. Salmonella infections can cause enteric fever, gastroenteritis, septicemia, and non-typhoidal Salmonellae (NTS) infections, especially in immunocompromised patients. Objective: To determine the Minimum Inhibitory Concentration (MIC) of Tigecycline against Salmonella Typhi. Methodology: This interventional study conducted at Department of Pharmacology & Therapeutics in collaboration with Department of Microbiology at Ad-din Sakina Women’s Medical College, Jashore during March 2023 to April 2023.MIC of Tigecycline was determined by Broth Dilution Technique against standard strain of Salmonella typhi ATCC 24683. Result: The MIC of Tigecycline against Salmonella typhi was 2.0 μg/ml. Conclusion: Tigecycline is a potential therapeutic agent for Salmonella typhi infection, and should be restricted on the basis of blood culture and in MDR and XDR cases of typhoid fever only. The Journal of Ad-din Women’s Medical College; Vol. 11 (2), July 2023; p 15-19